2018
DOI: 10.7717/peerj.4607
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of anthocyanin-related genes reveals effects of light intensity on anthocyanin biosynthesis in red leaf lettuce

Abstract: Red leaf lettuce (Lactuca sativa L.) is popular due to its high anthocyanin content, but poor leaf coloring often occurs under low light intensity. In order to reveal the mechanisms of anthocyanins affected by light intensity, we compared the transcriptome of L. sativa L. var. capitata under light intensities of 40 and 100 μmol m−2 s−1. A total of 62,111 unigenes were de novo assembled with an N50 of 1,681 bp, and 48,435 unigenes were functionally annotated in public databases. A total of 3,899 differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…The enhanced abundance of transcripts of chalcone synthetase, flavanone 3-hydroxylase, and anthocyanin synthetase seen in some black varieties implied a strong correlation between transcription and pigment content. Sun et al (2018) found that flavonoid pathway genes were regulated by ternary MYB-bHLH-WD40 transcriptional complexes Zhang et al, 2018). A microarray-based comparison of black and white rice identified nearly 1,300 differentially transcribed genes, of which 137 were predicted to encode transcription factors belonging to 1 of 10 different classes .…”
Section: 'Omics Approaches Taken To Unraveling the Mechanistic Basis mentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced abundance of transcripts of chalcone synthetase, flavanone 3-hydroxylase, and anthocyanin synthetase seen in some black varieties implied a strong correlation between transcription and pigment content. Sun et al (2018) found that flavonoid pathway genes were regulated by ternary MYB-bHLH-WD40 transcriptional complexes Zhang et al, 2018). A microarray-based comparison of black and white rice identified nearly 1,300 differentially transcribed genes, of which 137 were predicted to encode transcription factors belonging to 1 of 10 different classes .…”
Section: 'Omics Approaches Taken To Unraveling the Mechanistic Basis mentioning
confidence: 99%
“…Anthocyanin production in pigmented grain appeared to be induced and fine-tuned by BBX14 in conjunction with the basic leucine zipper transcription factor HY5. Both irradiation at a high light intensity and the plant's sugar content can influence anthocyanin and proanthocyanin synthesis Ma et al, 2018;Zhang et al, 2018). Therefore it would be of value to search for linkages between photoreceptor and light signal transduction elements associated with anthocyanin/proanthocyanidin synthesis in pigmented rice (Teng et al, 2005).…”
Section: 'Omics Approaches Taken To Unraveling the Mechanistic Basis mentioning
confidence: 99%
“…Light signaling components such as PIF3, CYR1, UVR8, and HY5 have been demonstrated to be key light signal transduction factors involved in anthocyanin biosynthesis under different light conditions [11][12][13][14]. Blue and UV-A light have also been reported to induce the expression of genes involved in anthocyanin biosynthesis in Brassica rapa [15,16], Litchi chinensis [17], Lactuca sativa [18], Arabidopsis [12], and Pyrus [19]. miRNAs negatively regulate the expression of genes involved in light-regulated processes [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed He, 2008;Wu et al, 2011;Zhang et al, 2018). Partial least-squares regression can reduce data noise and computation time, with only minor loss of the information contained in the original variables.…”
Section: Partial Least Squares Regressionmentioning
confidence: 99%
“…These compounds also play a photo-protective role (Liakopoulos et al, 2006), and act as optical barriers (Close & Beadle, 2003;. A number of environmental stresses, such as strong light, low temperature, UV-B irradiation, wounding, drought, bacterial and fungal infections, deficiencies in nitrogen, phosphorus and potassium, and certain herbicides and pollutants can result in the significant accumulation of anthocyanins (Saure, 1990;Garriga et al, 2014;Zhang et al, 2018), which are thus often referred to as "stress pigments" (Chalker-Scott, 1999). In addition, anthocyanins accumulate transiently in juvenile and senescing leaves in many plant species under unfavorable conditions (Karageorgou & Manetas, 2006;Merzlyak et al, 2008;Zeliou, Manetas & Petropoulou, 2009;Garriga et al, 2014).…”
Section: Introductionmentioning
confidence: 99%